Representatives Of The Hanafi Doctrine Mentioned In “Tabsirat Al-Adilla” (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the history of the formation of the Hanafi-Maturidi theological school and the issues related to its roots. It also provides a scholarly refutation of the views that this doctrine emerged at a later period. The research is based on classical sources such as “Tabsirat al-Adilla” and is structured around the analysis of the academic lineage of several generations of scholars from Transoxiana and Khurasan. The article demonstrates through chronological evidence that the chain of teachers of Imam al-Maturidi and his followers dates back to periods much earlier than that of Imam al-Ash’ari. In the course of the analysis, the legacy of mutakallimun and Sufi scholars such as Imam al-Tahawi, the Iyadi dynasty, and al-Kalabadhi is referenced, revealing the comprehensive nature of the doctrine. In conclusion, it is scientifically substantiated that Maturidism is an authentic theological school with a historically established and unbroken tradition.
Keywords: Maturidism; aqidah; kalam; Transoxiana; “Tabsirat al-Adilla; ” Abu Mansur al-Maturidi; Hanafi school; al-Kalabadhi; Mu’tazilites; refutation